The latest progression of N6-methyladenosine (m6A) RNA modification in diabetes mellitus and diabetic complications - Yin, Guangyang; Hong, Jiajing; Shan, Guohui; Xu, Cuizhu; Li, Bailin; Yang, Dongyu (Frontiers in Endocrinology, 2026)
The increasing global prevalence of diabetes mellitus and its complications continues to encourage exploration of novel molecular mechanisms for their prevention and treatment. N6-methyladenosine (m6A) is a methylation modification that occurs at the N6 position of adenosine in most RNAs and represents the most prevalent internal modification of eukaryotic messenger RNA. This dynamic and reversible modification is involved in regulating nearly all aspects of RNA metabolism and therefore plays important roles in various diseases, including diabetes mellitus and its complications. The present review summarizes recent advances in understanding the functions of m6A modification, its regulators, and potential downstream targets in diabetes mellitus and diabetic complications. Notably, different—and sometimes opposite—expression patterns and regulatory roles of m6A regulators have been reported within the same disease or among diabetes-related disorders. The heterogeneity of patient tissues, cell lines, and experimental models used across studies highlights the need for further comprehensive evaluation of the roles of m6A modification in diabetes mellitus and its complications. This review provides a valuable reference for tracking recent research progress in the field of m6A modification in diabetes mellitus.